TVET Systems' Response to COVID-19 Challenges and Opportunities - Hoftijzer, Margo (The World Bank, 2020)
This note focuses on the role of Technical and Vocational Education and Training (TVET) in the response to the COVID-19 pandemic. It provides guidance on reducing the adverse impact of the pandemic on TVET provision and enhancing the contribution TVET can make to mitigating the health, social, and economic impact of COVID-19